شرح الحدیث بالحدیث - Al-isnadi, Hafiz Zahir Ahmad; Akhter, Dr Naseer Ahmed (Al-Irfan, 2022)
In order to understand and explain the traditions of the Holy Prophet (peace and blessings of Allah be upon him), it is very important to know the related sciences. Otherwise, there is every chance that the interpreter will stumble around in the dark and never arrive at the destination. There are several ways to interpret a hadith such as: the explanation of a tradition through a tradition, the explanation of a tradition through the words of a Companion of the Messenger, the explanation of a tradition through the words of a Follower, and the explanation of a tradition through the Arabic language. Through this research article, we will try to understand the need and importance of “the explanation of a tradition through a tradition” and its principles and rules in the light of Holy Qur’an, the practices of the Messenger (peace and blessings of Allah be upon him) and the sayings of Imams. Both Scriptural verses and Prophetic traditions were revealed, and there are proofs from the Qur'an and Sunnah to establish the point. Scholars have given arguments in this regard which are too numerous to be covered.